2019
DOI: 10.1186/s12884-019-2215-9
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine exposure during pregnancy, small for gestational age birth and neonatal outcome – results from the Norwegian Mother and Child Cohort Study

Abstract: Background Maternal caffeine intake has repeatedly been linked to babies being born small for gestational age (SGA). SGA babies are known to be at increased risk for adverse neonatal outcomes. The aim of this study was to explore the associations between prenatal caffeine exposure and neonatal health. Methods The study is based on 67,569 full-term singleton mother-infant pairs from the Norwegian Mother and Child Cohort Study. Caffeine consumption from different sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
2
19
2
16
Order By: Relevance
“…No relationship between neonatal anthropomorphic parameters and caffeine intake in Poland was found in our previous study as well, where mean caffeine intake was <100 mg, which is similar to the findings in the present study [28]. According to the latest reports in the literature, in particular a study from Norway, daily caffeine intake of <200 mg increases the risk for small-for-gestational-age infant by 16% [37]. In a study from Ireland, a daily increase in caffeine intake by 100 mg resulted in a decrease in neonatal weight (by 72 g), length (by 0.3 cm), and head circumference (by 0.12 cm) [38].…”
Section: Discussionsupporting
confidence: 91%
“…No relationship between neonatal anthropomorphic parameters and caffeine intake in Poland was found in our previous study as well, where mean caffeine intake was <100 mg, which is similar to the findings in the present study [28]. According to the latest reports in the literature, in particular a study from Norway, daily caffeine intake of <200 mg increases the risk for small-for-gestational-age infant by 16% [37]. In a study from Ireland, a daily increase in caffeine intake by 100 mg resulted in a decrease in neonatal weight (by 72 g), length (by 0.3 cm), and head circumference (by 0.12 cm) [38].…”
Section: Discussionsupporting
confidence: 91%
“…57 Notably, similar and higher estimates of risk for SGA were reported in recent observational studies not included in the meta-analyses. Of three such studies, two reported good agreement for increased risk associated with moderate caffeine intake of 16% (95% CI 1.10 to 1.23) 74 and 18% (95% CI 1.10 to 1.27), 73 and the third reported an increased risk of 57% (95% CI 1.16 to 2.13) associated with higher intake. 4 Online supplementary table 1 shows that, of four observational studies published since 2000, two reported maternal caffeine consumption to be associated with increased risk of preterm birth 73 79 and two reported no association.…”
Section: Low Birth Weight (Lbw) And/or Small For Gestational Age (Sga)mentioning
confidence: 96%
“…[64][65][66] Although consumption in the order of 70 mg/kg or more per day has been typical for animal experiments, significant growth reduction in rat offspring has also been reported for as little as 10 mg/kg of daily caffeine (the approximate equivalent in humans of 7 cups of coffee). 67 Online supplementary table 1 shows that, of 13 observational studies comprising 12 cohort studies and one case-control study, four reported results for LBW alone, [68][69][70][71] three for SGA alone, [72][73][74] and six for both outcomes. 4 75-79 Of the 10 studies reporting results for LBW, seven reported caffeine-related increased risk 4 68-71 77 78 and three reported no association.…”
Section: Low Birth Weight (Lbw) And/or Small For Gestational Age (Sga)mentioning
confidence: 99%
“…En cuanto al consumo de substancias lícitas durante el embarazo, los datos de prevalencia del consumo de cafeína en la literatura son muy limitados a pesar de ser la substancia psicoactiva más ampliamente consumida en el mundo (Kuczkowski, 2009). En nuestra muestra, un 40% de las mujeres embarazadas tomaban de media 1-2 tazas de café al día, acercándose a los niveles descritos de cafeína (> 200mg/dia) que se asocian con efectos negativos sobre el embarazo y el periodo perinatal (Chen, Bell, Browne, Druschel y Romitti, 2014;Modzelewska et al, 2019), recomendándose reducir la ingesta de cafeína al mínimo durante el embarazo (Jahanfar y Jaafar, 2013).…”
Section: Prevalencia De Consumo De Sustancias Legales E Ilegales Duraunclassified